2007
DOI: 10.1111/j.1365-2982.2006.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rapid swallowing in idiopathic achalasia: evidence for patients’ heterogeneity*

Abstract: In order to evaluate the function of inhibitory neural pathways in achalasia, we compared the response of the oesophageal body and lower oesophageal sphincter (LOS) to single swallows (SS) and multiple rapid swallowing (MRS) in 20 consecutive patients with untreated idiopathic achalasia (10 men, aged 23-81 years) and in 20 control patients without dysphagia (nine men, aged 31-73 years), using sleeve manometry; 277 SS and 85 MRS were analysed. In the control group, MRS inhibited motor activity in the oesophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…In the symptomatic patients, in whom 4s IRP was more variable after SS and >15 mmHg in two, MRS decreased 4s IRP presumably as a result of greater stimulation of the inhibitory neural pathways, as suggested by previously published traditional manometry data [5]. In the achalasia patients, 4s IRP was higher than in healthy subjects and did not change after MRS, most likely because of severe damage to the inhibitory neural pathways.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In the symptomatic patients, in whom 4s IRP was more variable after SS and >15 mmHg in two, MRS decreased 4s IRP presumably as a result of greater stimulation of the inhibitory neural pathways, as suggested by previously published traditional manometry data [5]. In the achalasia patients, 4s IRP was higher than in healthy subjects and did not change after MRS, most likely because of severe damage to the inhibitory neural pathways.…”
Section: Discussionmentioning
confidence: 65%
“…Each test started with eight 5 mL single swallows (SS) of water at intervals of 20-30 s, followed by two 10 mL MRS as follows: swallows of 2 mL of water were administered through a syringe at intervals of 2-3 s, while the physician indicated the rhythm of swallowing [5]. Finally, one multiple rapid swallowing of 200 mL of water within 30 s was administered using a straw [8].…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…3). A normal response to multiple rapid swallowing requires on the one hand indemnity of inhibitory and excitatory mechanisms and on the other hand, esophageal muscle indemnity able to respond to a strong stimulation at the end of the MRS. As expected, multiple rapid swallowing induced an abnormal response in patients with achalasia 63. In contrast, symptomatic patients (dysphagia, chest pain or heartburn) with normal standard manometry showed preserved inhibition during MRS with a more significant abnormality in the post-MRS after contractions 64…”
Section: Deglutitive Inhibition and Primary Esophageal Motor Disordersmentioning
confidence: 62%
“…Katz et al (9), in a series of 23 patients with achalasia, noted that 7 of 23 (30%) patients had normal mean LES relaxation. Manometric LES heterogeneous response has also been demonstrated by studying the response to deglutitive inhibition in patients with achalasia (22). Also, recent data obtained from studies using high-resolution manometry (HRM) have also suggested that there is heterogeneity in the type of manometric abnormalities seen in adults with achalasia (17,23).…”
Section: Discussionmentioning
confidence: 96%